OPTIMALISASI DOSIS PUPUK NPK PHONSKHA PADA PERTUMBUHAN DAN HASIL TANAMAN BABY CORN JAGUNG MANIS (Zea Mays Saccharata Struth): - - Sukmawati (Faculty of Agriculture Science & Technology, 2023)
Baby corn is a vegetable that is widely consumed and in great demand by the public. Baby corn can be produced from any type of corn and does not require special growing conditions. Baby corn can grow and develop in all types of soil, especially in fertile soil. Maximum growth and yield of baby corn is sought by maintaining soil fertility through fertilization. The recommended fertilizer is Phonska NPK fertilizer. This study aims to determine the effect of Phonskha NPK Fertilizer Dosage on the Growth and Yield of Baby Corn Sweet Corn (Zea Mays Saccharata Sturt). The research design used in this study was a completely randomized design (CRD) with one treatment, namely the dose of NPK Phonska (P) fertilizer which consisted of five treatment levels, namely: P0: Control, P1: 50 kg/ha, P2: 100 kg/ha , P3: 150 kg/ha, P4: 200 kg/ha. Each treatment was repeated 3 times with each experimental unit consisting of 2 sample plants to obtain 30 experimental pots. The results showed that only the number of leaves parameter was not significantly different from the 4 parameters that were the focus of the experiment. Of the 4 experimental parameters observed, the highest growth and yield of baby corn was indicated by the P4 treatment level (200 kg/ha of Ponskha NPK fertilizer). The application of NPK Phonska fertilizer at 200 kg/ha is optimum for the growth and yield of sweet corn baby corn. Phonska NPK fertilizer dose of 200 kg/ha can increase plant height, fruit diameter, fruit length and fruit weight. The presence of Nitrogen, Phosphorus and Potassium available in Phonska NPK fertilizer greatly supports plant growth and yield (plant height, number of leaves, flowers, fruits and seeds). Plants require balanced N, P and K nutrients for optimal growth.